NUMERICAL STUDY OF T-JOINT DAMAGE IN SANDWICH COMPOSITE STRUCTURE UNDER QUASI-STATIC LOADING - Fitriyah, Lailatul
Composite sandwich structure T-joint have an important function in seaplane float structures in connecting and transferring loads from the hull panel to the bulkhead. Failure of the T-joint can result in a fatal accident. Therefore, it is needed to study T-joint damage to ensure the integrity of the sandwich structure. With the current advancement of computing technology, numerical modeling can already be done to solve this prolem. Therefore, development time and costs can be significantly reduced, and the number of tests that require complex preparation and large costs also can be reduced. Numerical modeling methods in this study is done to observe the failure modes of T-joint in the form of delamination, core crushing, and core shearing by using cohesive element, crushable foam, and element deletion on ABAQUS/CAE software. Damage initiation will be modeled by using traction- separation response in adhesive layer and ductile damage in foam material. The validation process was carried out by comparing the result of the T-joint experiment from the literature with low velocity impact loading. The T-joint model of amphibious airplane float would be given quasi-static loading and analyzed the failure that occurred. The numerical simulation result of this study have been able to visualize the failure to approach the results of the experimental result done by Umut,etc [1]. This shows that the modelling and parameters that used in this numerical simulation can represent the T-joint damage mechanism in real-life condition.